Education, heritage and identities in Europe understanding Europe's current predicaments - Kaya, Ayhan; Tecmen, Ayşe; Balatlıoğulları, Didem (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
Lesson Plan for Chapter 1: “Space and Identity: Mapping Europe in an Age of Crisis”......................... 1 Lesson Plan for Chapter 2: “Europe and the European Union in Geographic Education Curricula: A Case Study” ........................................................................................................................................................ 5 Lesson Plan for Chapter 3: “European Economic Integration and the Debt Crisis” ............................ 9 Lesson Plan for Chapter 4: “Europe, Migration and the Refugee Crisis” ............................................. 14 Lesson Plan for Chapter 5: “Europe on Display: a Case Study” .............................................................. 19
24 pages